Carta de Roberto H. Todd a Horace M. Towner - Todd, Roberto H.; Towner, Horace M. (My University, 1922)
Asuntos político
Keywords: Puerto Rico--Politics and government.; Puerto Rico--Política y gobierno.; Mc Clure, George; Montgomery Reily, Emmet, 1866-1954; Córdova Dávila, Félix, 1878-1938; Towner, Horace Mann, 1855-1932; Barceló, Antonio R., 1868-1938